Dienogest or Norethindrone acetate for the treatment of ovarian endometriomas: Can we avoid surgery?. (July 2019) - Del Forno, Simona; Mabrouk, Mohamed; Arena, Alessandro; Mattioli, Giulia; Giaquinto, Ilaria; Paradisi, Roberto; Seracchioli, Renato
Abstract: Objective: To compare the effects of Dienogest (D) and Norethindrone acetate (N) in symptomatic women with ovarian endometriomas, analyzing the efficacy in reducing endometrioma size and symptom relief and drug tolerability. Study design: Retrospective study including 135 symptomatic women with ultrasonographic diagnosis of ovarian endometrioma. Women were divided into two groups: 1) women who received D 2 mg/day (group D); 2) women who received N 2.5 mg/day (group N). Women were evaluated at therapy prescription and after 6 and 12 months of treatment: transvaginal ultrasound was performed to assess the mean diameter of endometriomas, a Visual Analogue Scale was used to rank endometriosis related symptoms (dysmenorrhea, dyspareunia, chronic pelvic pain). The main outcome measure was the comparison between the 2 groups in terms of variations in endometrioma size and endometriosis related symptoms during the follow-up. Drug tolerability was also analyzed in terms of side effects. Results: A reduction in ovarian endometrioma size was observed during treatment in both groups, with no significant differences between groups D and N. Endometriosis related symptoms decreased in both groups, but the decrease was significantly higher in group D than in group N for all symptoms, both at 6 and 12 months of treatment. Regarding drug tolerability, uterine bleeding/spotting and weight gain were reported more frequently by women in the group N than women in the group D, both at 6 and 12 months of treatment. Conclusion: Progestin therapy with D or N appears to be effective in reducing the size of endometriomas and related symptoms, with a greater effect on symptoms relief and higher tolerability in women treated with D.